A Cross-Cultural Study of Filial Piety and Palliative Care Knowledge: Moderating Effect of Culture and Universality of Filial Piety - Li, Wendy Wen; Singh, Smita; Keerthigha, C. (Frontiers in Psychology, 2021)
Filial piety is a Confucian concept derived from Chinese culture, which advocates a set of moral norms, values, and practices of respect and caring for one’s parents. According to the dual-factor model of filial piety, reciprocal and authoritarian filial piety are two dimensions of filial piety. Reciprocal filial piety is concerned with sincere affection towards one’s parent and a longstanding positive parent-child relationship, while authoritarian filial piety is about obedience to social obligations to one’s parent, often by suppressing one’s own wishes to conform the demands of the parent. The primary aim of this study is to investigate the moderating effect of culture on the relationships between filial piety and palliative care knowledge. The secondary aim is to investigate whether filial piety is a universal construct across Singaporean and Australian cultures. The final sample of the study comprised of 406 participants, with 224 Singaporeans and 182 Australians. There were 289 females (71.1%), 115 males (28.3%), and two unspecified gender (0.6%) in the sample, with an average age of 27.27 years (SD = 9.79, range = 18-73). Results indicated a significant effect of culture on authoritarian filial piety and palliative care knowledge. Singaporeans showed higher authoritarian filial piety and higher palliative care knowledge than Australians. However, no effect of culture was found on reciprocal filial piety. Overall, no significant correlation existed between palliative care knowledge and reciprocal filial piety and authoritarian filial piety. For Singaporeans, a weak negative correlation was found between palliative care knowledge and authoritarian filial piety. In contrast, Australians and Singaporeans indicated a positive, moderate correlation between reciprocal and authoritarian filial piety. Further, culture moderated the relationship between authoritarian filial piety and palliative care knowledge. High authoritarian filial piety was associated with increased palliative care knowledge among Australians, while high authoritarian filial piety was associated with decreased palliative care knowledge among Singaporeans. The results support the conceptualization of filial piety as a possible psychological universal construct. In addition, the results point out an important implication that public health programs should target the appropriate filial piety types to enhance palliative care knowledge among Singaporeans and Australians.